Infectious complications of induction treatment for acute myeloid leukaemia using the ``7 + 3'' protocol without antibiotic prophylaxis - 15 years of experience of one clinical site - Cernan, Martin; Szotkowski, Tomas; Hubacek, Jaromir; Kolar, Milan; Faber, Edgar; Indrak, Karel; Papajik, Tomas (Biomedical papers, 2023)
Background. Infectious complications during induction chemotherapy of acute myeloid leukaemia are very common. Prophylactic use of antibiotics however is an ongoing challenge in this situation due to bacterial multi-drug resistance. The aim of this study was to provide a comprehensive overview of the incidence of infectious complications in patients with AML undergoing induction therapy using the ``7+3'' protocol without routine antibiotic prophylaxis at one clinical site providing specialised haematological care in the Czech Republic, over a period of 15 years. The study also evaluates the aetiological spectrum of causative agents and the development of antibiotic resistance in the context of the use of the various classes of antibiotics. The analysis includes evaluation of the importance of risk factors for infectious complications and their impact on treatment of the underlying disease. The data are compared with published figures for similar cohorts of patients. Patients and Methods. This study presents a retrospective analysis of infectious complications in 242 patients with acute myeloid leukaemia undergoing the first cycle of induction therapy without routine antibiotic prophylaxis in one clinical site in Czech Republic during years 2006-2020. Results. A total of 363 febrile episodes (FE) were recorded. At least 1 FE during the induction was detected in 229 (94.6%) patients. Clinically defined infection was the cause in 96 (26.4%) FEs and blood stream infection in 69 (19.0%) FEs. Both complications occurred simultaneously in 29 (8.0%) FEs. 169 (46.6%) FEs were evaluated as fever of unknown origin (FUO). The achievement of complete remission had a significant effect on the duration of the FE (6 vs. 9 days, P=0.0005) and on the overall survival duration (79.3 vs. 6.5 months, P<0.0001). Patients diagnosed with infection or FUO at diagnosis were significantly more likely to suffer from colonisation by multi-drug resistant bacterial strains at discharge (29.2% vs. 16.3%, P=0.022). This group of patients used antibiotic therapy for a significantly longer time (35 vs. 23 days, P<0.0001). Infection was a contributing cause of death in 18 (7.4%) patients. Mortality was significantly related to the failure to achieve complete remission (P<0.0001). Conclusion. Infectious mortality during induction treatment without routine antibiotic prophylaxis was comparable to the published cohorts with prophylaxis. Regular microbiology surveillance with adequate initial antibiotic treatment can compensate routine antibiotic prophylaxis with slower development of antibiotic resistance.
Keywords: acute myeloid leukaemia; induction therapy; infectious complications; antibiotic prophylaxis; antibiotic resistance; mortality